Uma visão retrospectiva e sistemática dos efeitos e dos impactos da quimioterapia em cães - Coelho, Yasmin Nascimento Bernardes (2023)
This retrospective study involved an analysis of 182 dogs between June 2018 and December 2021, which underwent chemotherapy treatment at the UFU Veterinary Hospital. The main objective was to identify the epidemiological profile of these dogs, considering a variety of factors, such as breed, age, gender, weight, size, body score, neutering status, diagnosis, clinical staging, histological grade, tumor location and size, type of chemotherapy treatment used, adverse effects, and blood and biochemical tests. The research broadly addressed the characteristics of the treatments, including the main drugs, dosages, occurrence and reasons for discontinuation of treatment, as well as the adverse effects and changes in blood and biochemical parameters caused by chemotherapy treatment. The main findings revealed that most of the dogs in the sample were neutered, undefined breed and female, with ages predominantly between 9 and 12 years. The most common diagnoses were Transmissible Venereal Tumor (TVT) and mast cell tumor. As for chemotherapy treatments, the most frequent involved the use of vincristine, carboplatin and vinblastine. The most prevalent adverse effects included neutropenia, vomiting and diarrhoea, with neutropenia often leading to discontinuation of treatment. Neutropenia occurred mainly after the first treatment session, with a predominance of grade I cases. Factors such as the size of the dogs and the treatment protocol used were found to be associated with the risk of developing neutropenia. With regard to hematological and biochemical parameters, it was observed that the use of vincristine resulted in a significant reduction in segmented neutrophils during treatment, compared to the post-chemotherapy period. Vinblastine, on the other hand, showed reductions in hematocrit count and red blood cell count during treatment, compared to the pre-chemotherapy period. The current gold standard treatment for canine mast cell tumors (MCT) uses vinblastine sulfate (VBL) as chemotherapy, although tyrosine kinase inhibitors (TKI) have recently been shown to be worthy candidates for the treatment. This systematic review aimed to analyze overall survival (OS), progression-free survival (PFS), overall response rate (GRT), and complete (CR) or partial (PR) response in MCT dogs treated with TKI compared to standard VBL treatment. The systematic review was registered in the Open Science Framework (OSF) database under the identifier 10.17605/OSF. IO/WYPN4 (https://osf.io/). An electronic search was conducted in nine databases. References from eligible studies were also screened to find more records. A total of 28 studies met the eligibility criteria, and one more was retrieved from the references of eligible studies, for a total of 29 selected studies. The overall response (50.36%), complete response (26.49%), and partial response (39.46%) rates were higher in dogs treated with tyrosine kinase inhibitors compared to dogs treated with vinblastine, where these rates were 28.75%, 23.21%, and 36%, respectively. The duration of overall survival (524 days) and progression-free survival (714 days) of dogs receiving vinblastine treatment was longer than that observed in dogs receiving tyrosine kinase inhibitors, which achieved an overall survival of 308 days and a progression-free survival of 207 days, respectively. Dogs with mutated KIT treated with tyrosine kinase inhibitors have higher overall survival and progression-free survival compared to those treated with vinblastine.